EFFECTIVENESS OF SIMULATION-BASED LEARNING AMONG NURSING STUDENTS: EVIDENCE PRACTICE (EBP) PROJECT ON CARDIOPULMONARY RESUSCITATION SKILLS CPR (The Research of Medical Science Review, 2025)
Background and Aim: Cardiopulmonary resuscitation is a critical and life-saving skill in a nursing practice, and every nurse should be competent in performing CPR at a time of medical emergency. Traditional methods of teaching CPR often lack hands-on practice, competence, and confidence for nursing students. Simulation-based learning (SBL) has emerged as an innovative educational strategy to provide a realistic, risk-free environment for practicing clinical skills. The aim of this evidence-based project is to evaluate the effectiveness of simulation-based learning in enhancing CPR skills among nursing students. Methods: This project was conducted in the nursing department on 12 students of the 7th semester of BSc Nursing. A pre- and post-interventional study was conducted using a standard American Health Association (AHA) checklist for CPR skill. PubMed and CINAHL databases were used for a comprehensive literature review. Results: Data was analyzed through SPSS version 23. A paired T-test was used, which showed that the mean of post-intervention was 17.33, which is about three times more than that of pre-intervention, which were 6.50. Conclusion: Simulation-based learning is more effective in improving the competency level of nursing students in clinical practices.